Predator-by-Environment Interactions Mediate Bacterial Competition in the Dictyostelium discoideum Microbiome - Inglis, R. Fredrik; Asikhia, Odion; Ryu, Erica; Queller, David C.; Strassmann, Joan E. (Frontiers in Microbiology, 2018)
Interactions between species and their environment play a key role in the evolution of diverse communities, and numerous studies have emphasized that interactions among microbes and among trophic levels play an important role in maintaining microbial diversity and ecosystem functioning. In this study, we investigate how two of these types of interactions, public goods cooperation through the production of iron scavenging siderophores and predation by the social amoeba Dictyostelium discoideum, mediate competition between two strains of Pseudomonas fluorescens that were co-isolated from D. discoideum. We find that although we are able to generally predict the competitive outcomes between strains based on the presence and absence of either D. discoideum or iron, predator-by-environment interactions result in unexpected competitive outcomes. This suggests that while both cooperation and predation can mediate the competitive abilities and potentially the coexistence of these strains, predicting how combinations of different environments affect even the relatively simple microbiome of D. discoideum remains challenging.